Retrospective correction of physiological noise in DTI using an extended tensor model and peripheral measurements. Issue 2 (30th August 2012) - Mohammadi, Siawoosh; Hutton, Chloe; Nagy, Zoltan; Josephs, Oliver; Weiskopf, Nikolaus
<x xml:space="preserve">Abstract</x> Diffusion tensor imaging is widely used in research and clinical applications, but this modality is highly sensitive to artefacts. We developed an easy‐to‐implement extension of the original diffusion tensor model to account for physiological noise in diffusion tensor imaging using measures of peripheral physiology (pulse and respiration), the so‐called extended tensor model. Within the framework of the extended tensor model two types of regressors, which respectively modeled small (linear) and strong (nonlinear) variations in the diffusion signal, were derived from peripheral measures. We tested the performance of four extended tensor models with different physiological noise regressors on nongated and gated diffusion tensor imaging data, and compared it to an established data‐driven robust fitting method. In the brainstem and cerebellum the extended tensor models reduced the noise in the tensor‐fit by up to 23% in accordance with previous studies on physiological noise. The extended tensor model addresses both large‐amplitude outliers and small‐amplitude signal‐changes. The framework of the extended tensor model also facilitates further investigation into physiological noise in diffusion tensor imaging. The proposed extended tensor model can be readily combined with other artefact correction methods such as robust fitting and eddy current correction. Magn Reson Med 70:358–369, 2013. © 2012 Wiley Periodicals, Inc.